Success Stories as Essential Tool for Tuberculosis Awareness Creation on Social Media: A Case Study of KNCV Nigeria - Onyinye Kene-Eneh; Bethrand Odume; Chidubem Ogbudebe; Ogoamaka Chukwuogo; Debby Nongo; Amarachi Obinna-Nnadi; Cyril Dim; Jumoke Adebari; Chukwuma Anyaike (Nigerian Journal of Medicine)
Background: In 2022, KNCV Nigeria’s social media messaging strategy leading up to World Tuberculosis Day (WTBD) shifted from organisational stories to success stories. Objective: The objective of this study was to compare the impacts of the pre-WTBD social media messages used before 2022 (organisational stories) with the type used in 2022 (success stories). Materials and Methods: The reach and engagement of the KNCV Nigeria pre-WTBD organisational stories for 2021 and success stories for 2022 were retrieved from Facebook and Instagram and compared. Results: The reach of the success stories was 18,297 persons while that of organisational stories was 7817 persons. Furthermore, the overall engagement of 795 in 2022 was significantly higher than 267 in 2021 (P < 0.001). Conclusion: KNCV Nigeria’s pre-WTBD success stories reached a significantly larger audience and generated higher engagement on social media organisational stories.